Smart mosques prayer display and apps / Muhammad Shahir Hakimy Salem - Salem, Muhammad Shahir Hakimy (2019)
This paper is about a prayer's timetable system based on Internet Of Things (IoT). IoT promises a connection between (inter-) various things that prove service to humans and machines. This system has one web display, video recording and application. Each one is connected through the IoT system. Video recording system can be active by pressing ON switch. Videos that have been recorded will be stored in raspberry pi and databases. The web display will display prayer's timetable and information of the mosque. Other than that, the application also can display prayer's timetable, information of the mosque and video. Users can view the video through the application in the smartphone. In addition, users can see the tentative or mosque activity besides seeing prayer time in the application. So in this system, people around can easily find their prayer's time and people around get closer to mosque.